Physiological activation of plasminogen in full term newborn infants. - Hilali, M M (1984)
Plasminogen in full term newborn infants has been measured by functional and immunological assays. Plasminogen functional activity and antigen concentration in newborn infants were about 44% and 48% of adult values respectively. Physiological activation kinetics of plasminogen in undiluted plasma at pH 7.4 and 37 degrees C using various concentrations of streptokinase and urokinase showed no significant difference in the rate of plasmin generation between plasminogen from newborn infants and adult plasminogen. These findings dispute the suggested existence of functional anomalies in plasminogen from full term newborn infants.